Initial experience in trans-radial percuteneous coronary intervention - Mttansh, .Ali Hussein; Bairm, .Amjad R.; Abbas, .Nazer (AL-Kindy College Medical Journal, 2015)
Background: Transradial compared to classic transfemoral coronary intervention has been shown to have similar efficacy rates, while being more cost-effective and most importantly safer due to fewer access site complications. Furthermore, patient comfort is increased and outpatient treatment may be feasible..Objectives: To start trans-radial intervention program and the initial learning curve for fellows and the catheterization –laboratory nursing staff. To test how could it be applicable and comfortable for our patientsMethods: This prospective study was performed in Ibn-Albitar hospital for cardiac surgery over a period of 6 months from the 1st of August 2012 till the 1st of February 2013. Every patient referred for percutenuos coronary intervention whether on scheduled or on an emergency basis was considered initially for trans-radial approach for intervention unless they are excluded. Allen test was required ensuring adequate ullnar collateral supply. Sledinger technique was used for radial artery puncture and a special radial sheath was introduced. Intervention was performed through the same catheter and equipments that are used for femoral approach.. medication given according to center protocol, the relevant data collected and patients immediately ambulated unless they receive sedation.Results: A total of 126 patients were referred for intervention during the study period, 20 cases were excluded for various reasons , 6caese were crossed over to femoral approach and the other 100 cases the procedure completed transradially. The mean age of the patients was 57 ± 8 years. Of these 72% were males ,with different risk factors . Most cases presented with chronic stable angiana (87%). Access site was right radial artery in 87% of patients while left radial approach used in 13% of patients. In 72% of cases single guiding catheter was used, in 21% of cases 2 guiding catheter were used and more than 2 types of guiding catheter were used in 7% of cases. In most session of intervention single artery was treated (78%) , 2 vessel intervention in 21%, 3 vessel in one case..Lesions treated were different types 26%,36%,38% A,B and C respectively. The success in obtaining radial access was 97.7% ,while angiographic procedural success rate was 96%. Mean total procedure time was ( 43+/-23min ), mean fluoroscopy time (13+/-8 min )and the average amount of contrast used was (178+/-80ml). with no major complication apart from 3% small heamatom and 6% radial loss. Around 80% of patients preferred TRI approach.Conclusion: Radial artery approach for percutenuos coronary interventions has high procedural success rate and associated with low risk of access site complications and no significant increase of procedural and fluoroscopy time. It is comfortable approach for most patients especially female and obese. Early ambulation with no risk of bleeding and reduction of the duration of hospital stay are in favor of TRI approach.